Pengaruh Motivasi Kerja, Disiplin Kerja, dan Gaya Kepemimpinan Terhadap Kinerja Guru (Studi pada Guru SMA Negeri 4 Kota Tangerang Selatan) - Hadi, Carrissa Nathaniela; Hari Subagio (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the effect of work motivation, work discipline, and leadership style on teacher performance. The research method used in this study is quantitative. The sample in this study consists of 52 teachers of SMA Negeri 4 Kota Tangerang Selatan. Data were collected through questionnaires using a Likert scale and were processed using Microsoft Excel 2021 and SPSS software version 26. The sampling technique used in this study is non-probability sampling using saturated sampling. The research method used is multiple linear regression analysis. The results of this study indicate that the variables of work motivation and leadership style have a significant effect on teacher performance, while work discipline does not have a significant effect on teacher performance.